Penerapan Psikologi Belajar Dalam Pembelajaran Anak TPA di TPA Fajrul Islam Kota Palembang: Menggunakan Metode Kooperatif - Luthfia Zahrotul Usythuriyah; Syailely Amalia CH; ⁠Malika Putri; Nadila Indriani; Dallah Dzakiah (CV. Doki Course and Training, 2026)
Qur’anic education for children requires flexible instruction tailored to variations in ability, attention, and motivation. Initial observations at Fajrul Islam Qur’anic Education Center in Palembang revealed that several students were easily distracted, quickly bored, and showed limited interest in Iqra’ reading and memorization. This descriptive qualitative study evaluated the implementation of learning psychology principles combined with flexible cooperative learning, alongside its impact on student engagement, confidence, and social behavior. Involving approximately 80 students, the researcher actively participated in reading, writing, numeracy, and memorization activities. Cooperative learning was adaptively structured using pair work, small groups, and peer tutoring. Learning psychology principles were integrated through emotional recognition, motivation, positive reinforcement, ice-breaking, songs, and educational games. Data collected via participatory observation and documentation were analyzed through data condensation, display, and conclusion drawing. The findings revealed positive behavioral shifts: students became more active, enthusiastic, confident, and collaborative. Furthermore, dynamic activities created an enjoyable, non-monotonous environment. Nevertheless, certain students still required ongoing individual guidance to sustain focus and participation. Ultimately, flexible cooperative learning grounded in learning psychology proves effective in fostering engaging, inclusive, and developmentally appropriate Qur’anic instruction.